Digital Transformation in Strengthening the Pedagogic and Professional Competence of Madrasah Teachers through the Utilization of Service Administration Information System (SIAP) - Muhibut Tibri; Rahmat Hidayat; Jamilus Jamilus (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid development of digital technology has encouraged madrasahs to adopt information systems to improve educational services and teacher performance. This study aims to identify and analyze the planning, implementation, and evaluation of the utilization of the Administrative Service Information System (SIAP) in improving the pedagogical competence and professionalism of madrasah teachers. A qualitative approach with a case study design was employed. Research participants consisted of madrasah principals, teachers, SIAP operators, and administrative staff involved in system implementation. Data were collected through in-depth interviews, observations, and documentation studies and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings indicate that SIAP utilization was systematically planned through needs assessment, program design, infrastructure preparation, and user training. Its implementation improved administrative efficiency, facilitated access to educational information, reduced teachers’ administrative workload, and enabled greater focus on teaching and learning activities. Furthermore, the system contributed to enhancing teachers’ digital literacy and professional competence. Regular evaluation through monitoring, supervision, and user feedback helped identify challenges and improve system effectiveness. Overall, SIAP positively contributes to strengthening pedagogical competence, teacher professionalism, and the digital transformation of madrasah education.